1997
DOI: 10.1111/j.1151-2916.1997.tb03243.x
|View full text |Cite
|
Sign up to set email alerts
|

Solid Solubility of Neodymium in BaCeO3

Abstract: Incorporation of Nd into the BaCeO3 perovskite structure was studied by quantitative wavelength dispersive spectroscopy‐electron probe microanalysis (WDS/EPMA) in combination with scanning electron microscopy (SEM) and X‐ray powder diffractometry (XRPD). Highly Nd‐doped BaCeO3 specimens, synthesized by mixed oxide technology, were sintered at 1400°C in ambient air. Concentrations of cations obtained by microanalysis were calculated to the ABO3 perovskite formula, considering incorporation of Nd at Ba as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…The result obtained here for the Nd doped sample is in excellent agreement with that reported by Makovec et al in their phase equilibria study of BaCeO 3 -Nd 2 O 3 . 9 The existence of the fluorite phase in the nominally stoichiometric Yb-doped sample (SSR) is consistent with the highly B-site specific manner in which this dopant is incorporated into barium cerate. Even slight barium oxide loss from this compound upon high temperature processing cannot be accommodated by dopant partitioning.…”
Section: B Phase Relationships and Stoichiometrymentioning
confidence: 73%
See 1 more Smart Citation
“…The result obtained here for the Nd doped sample is in excellent agreement with that reported by Makovec et al in their phase equilibria study of BaCeO 3 -Nd 2 O 3 . 9 The existence of the fluorite phase in the nominally stoichiometric Yb-doped sample (SSR) is consistent with the highly B-site specific manner in which this dopant is incorporated into barium cerate. Even slight barium oxide loss from this compound upon high temperature processing cannot be accommodated by dopant partitioning.…”
Section: B Phase Relationships and Stoichiometrymentioning
confidence: 73%
“…(1), in which the entirety of the dopant species resides on the B-site of the perovskite oxide, it has been shown (through a careful phase diagram study) that Nd in particular can be partitioned over both A-and B-sites of barium cerate ceramics in which the total Ba/(Ce+Nd) molar ratio is less than one. 9 Such an observation is perhaps not unexpected given the relative ionic radii of the three species involved, with Nd being intermediate in size between Ce and Ba. Experimental evidence for the existence of similarly "amphoteric" dopants in BaTiO 3 has also been recently reported.…”
Section: Introductionmentioning
confidence: 97%
“…The distribution of dopant into A site has been reported in pervskite-type oxides such as BaCeO 3 [29][30][31][32][33][34], BaTiO 3 [35][36][37], and CaZrO 3 [38,39] and SrZrO 3 [38] when the ionic radius of dopant is much larger than that of host cation of B site. Especially, in case of barium cerate, it is reported that La, Nd, Gd and Yb were partially substituted for A site (barium site) by atomistic simulation [31,34], and combination with XRD and WDS [29,32] and EXAFS [33] and that the amount of trivalent cation substituted for A site increases as the ionic radius of the trivalent cation becomes larger than that of cerium ion [33].…”
Section: Discussionmentioning
confidence: 99%
“…Studying the phase equilibrium of the Nd 2 O 3 -BaCeO 3 system, Makovec et al 41 proved experimentally that through the microanalysis of the formed solid solutions, they could be represented by a general formula Ba 1-x Nd x Ce 1-y Nd y O 3-(y-x)/2 , in which the Nd 3+ ion occupies both Ba 2+ and Ce 4+ sites. The ratio between the amounts of Nd 3+ incorporated at A-and B-sites is a function of the starting composition, varying from 1 in the part with larger CeO 2 content to 0.1 in the part with larger BaO content of the BaO-CeO 2 -Nd 2 O 3 system.…”
Section: Defect Chemistrymentioning
confidence: 99%